Biodiversity of Saccharomyces cerevisiae populations in Malbec vineyards from the “Zona Alta del Río Mendoza” region in Argentina - Mercado, Laura Analia; Sturm, Maria Elena; Rojo, Maria Cecilia; Ciklic, Ivan Francisco; Martínez, Claudio; Combina, Mariana (Elsevier, 2019)
The “Zona Alta del Río Mendoza” (ZARM) is the major Malbec grape viticulture region of Argentina. The aim of the present study was to explore Saccharomyces cerevisiae biodiversity in ZARM vineyards. Interdelta PCR and RFLP mtDNA molecular markers were applied to differentiate S. cerevisiae strains. The presence of commercial strains on ZARM vineyards was also assessed. Our results reveal a highly diverse, but genetically closely related, S. cerevisiae population (containing more than 190 molecular patterns among 590 S. cerevisiae isolates). According to the S. cerevisiae strain diversity found in vineyards, they were classified as vineyards with high and low polymorphic S. cerevisiae populations. Six vineyards showed a high polymorphic population, with more than 20 different S. cerevisiae molecular patterns. S. cerevisiae populations in these vineyards were diverse and irregularly distributed, with different strains in each vineyard site. Low polymorphic S. cerevisiae population vineyards displayed very low yeast diversity, with only 9 to 10 different S. cerevisiae strains and presence of two commercial strains widely distributed. Population diversity estimators were calculated to determine the population structure of S. cerevisiae in the ZARM vineyards. The obtained values support the hypothesis that the eight sampled subpopulations come indeed from a larger population.